Integrated Simulation of Spillway and Diversion Structure in Flood Risk Assessment of Upper Solo River - Saraswati Renaningsih (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Wonogiri Reservoir is a multi-purpose hydraulic structure that is used for water supply service and flood control in the watershed area of Upper Solo River. Inflow of the Wonogiri Reservoir comes from 10 rivers in the watershed’s catchment area. As for the purpose of reservoir’s sediment controller, a new spillway is constructed; and also closure dike is being built, which influenced the change on reservoir storage characteristic, and then means that a new reservoir operation guideline is necessary. Therefore, study on flood routing on the watershed of Upper Solo River at the new condition of the reservoir operation is needed. The analysis was conducted to acquire detailed information on flood characteristics of Wonogiri Reservoir and Upper Solo River started from the downstream of the reservoir until the downstream control point in the Jurug Water Level Recorder including the flood discharge and the maximum water level. The analysis procedure was performed by four components, which are flood forecasting, reservoir flood routing, rainfall-runoff lateral inflow, and hydraulic channel routing. The analysis result was integrated into a software package which was arranged by using the Microsoft Visual Studio Express 2012, Microsoft Access, and HEC-RAS. With the support of the software, it was expected that the decision making in the spillway operational is more quickly and more accurate (rapid assessment) in order to improve the flood control performance in the area of Upper Solo River.